Surface characterisation of the corundum-route lead magnesium niobate ferroelectric ceramics - Laongnuan Srisombat (2018)
Perovskite relaxor ferroelectric PMN ceramics, Pb (Mg 1/3Nb 2/3O 3), have been fabricated using a two-stage process employing a corundum-type Mg 4Nb 2O 9 as a key precursor. The 100% perovskite PMN ceramics was revealed by X-ray diffraction analysis. The SEM image of the PMN ceramic shows irregular shape PMN grains on the porous surface. The surface chemical composition of the PMN ceramics could be characterized by X-ray photoelectron microscopy technique. The XPS results indicate most of the elements consist of more than one chemical species. The important of XPS studies here can reveal small amount of species which could not detected by XRD. © (2011) Trans Tech Publications.